Accurate detection method for compaction uniformity of asphalt pavement. (1st August 2017) - Zhang, Zhengqi; Huang, Shuolei; Zhang, Ke
Highlights: The reasonable detection interval of PQI is determined. The detection points in the road can be divided into high, medium and low density regions where the core samples are took according to proportion. The void distribution characteristic on sectional image of core sample is analyzed by image processing technology. The coefficients UCN and UCR are put forward to evaluate quantitatively compaction uniformity of asphalt pavement from the microscopic structure. Abstract: To evaluate the compaction uniformity effectively, firstly, the feasibility of using density and void distribution as compaction uniformity evaluation index was demonstrated by laboratory test. Secondly, relying on the project of Tong-Xun Highway, reasonable detection interval of non-nuclear density gauge PQI was determined, and quantitative evaluation index of density distribution uniformity was also proposed. Next, core samples at representative density point were drilled and of which the voids distribution characteristic on sectional image of core sample was analyzed by image processing technology, and further on, the evaluation index of void distribution uniformity was put forward. Finally, the accurate detection method of compaction uniformity based on density and void distribution was exampled relying on entitative engineering. The results show that it is feasible to evaluate the compaction uniformity of asphalt pavement with its density and void distribution. The reasonable lateral detection interval of PQI is 1.5 m, and the reasonable longitudinal detection space is 50 m. Density statistical index such as Sr, SR, k and h can reflect the density distribution uniformity on detection section. Voids number uniform coefficient UCN and voids ratio uniform coefficient UCR of core samples can reflect the compaction uniformity of asphalt pavement from the aspect of micro structure.